Patient reported outcome measure applicability in clinical oncology - Morelle, Alessandra Menezes; Venero, Fernando Castilho; Silva, Rommel Fabricio Pereira da; Ferreira, Rafael Dal Ponte; Santanna, Pedro Tofani (Brazilian Journal of Oncology, 2021)
Patient Reported Outcomes (PROs) are a report that comes from patients on a specific subject, describing how they feel about a condition or therapy. The term includes a range of constructions and methodology and can cover concepts such as symptoms to physical assessment, well-being and social involvement. The process can be described as a measure of patient reported outcome (Patient Reported Outcome Measure - PROM). In oncology, PROMs help healthcare professionals and systems to reduce the impact of treatment on patient's quality of life. In recent years, several studies have shown improvement in the evaluated outcomes. In our country, there is still little information on this subject, especially when it comes to cancer patients. Hence, we think that it is of utmost importance to review the particularities of this tool, in order to stimulate further discussion of the subject in our country.
Keywords: Patient reported outcome measures; Medical oncology; Quality of life.